CEO Characteristics, Board Gender Diversity, and ESG Performance: Evidence from Indonesia - Rahman, Zulfa Devina; Samiono, Bambang Eko; Gemilang, Reza Putra (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2024)
This study examines the impact of CEO characteristics and gender diversity on corporate ESG performance, focusing on Indonesian companies. The independent variables include CEO age, CEO tenure, CEO's technical or scientific expertise, female leadership in the board of directors, and female leadership in the board of commissioners. ESG performance measured by the ESG Risk Rating provided by Sustainalytics. A total of 262 samples were analyzed using a random effects panel data model (REM) with STATA 15. The results indicate that CEO age, CEO tenure, CEO's technical or scientific expertise, and female leadership in the board of directors do not significantly affect ESG performance. However, female leadership in the board of commissioners is found to have a significant impact. The findings suggest that increasing female representation on the board of commissioners can play a crucial role in reducing ESG risks, offering practical insights for policymakers and businesses aiming to enhance sustainability practices.